Developing a vaccine for a highly contagious cattle disease - Jores, Joerg (International Livestock Research Institute, 2012)
Contagious Bovine Pleuropneumonia (CBPP) is a highly contagious disease that affects cattle throughout most of sub Saharan Africa. It is one of the most serious livestock diseases with greatest impacts in pastoralist areas. Up to 15% of infected animals die: milk yields of infected cows drop by up to 90%: meat production is reduced, and infected draught oxen are less able to work. Existing vaccines have side effects and give limited protection. Research is underway at the International Livestock Research Institute (ILRI) to develop a more effective vaccine.